Analisis Kemampuan Membaca Siswa dengan Metode Sorogan di MI Salafiyah Syafi’iyah - Nasyiatul Lailiyah; Ahmad Halid (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Reading is an important component that students must have in learning activities. However, in reality, there are still students who cannot read well in the early grades or the final grades in elementary school, so a learning method is needed that can help facilitate students in reading. One of the learning methods used in this study is the sorogan method. The sorogan method is a learning method with individual tutoring. This research method uses qualitative descriptive research that aims to describe students reading abilities using the sorogan method. The subjects of this study were 10 students with the criteria of students who cannot read. Data collection in this study was in the form of observation, tests and documentation. Based on the research that has been done, it was found that the reading ability of MI Salafiyah Syafi'iyah students who applied the sorogan method had an average reading ability of very good. Of the 10 students, there are 6 students who have reading abilities with the criteria of Very Good, 2 students have reading abilities that are Quite Good and 2 students have reading abilities that are Not Good. The difficulties faced by students are that they cannot identify letters (vowels and consonants), read syllables, put words together into sentences, cannot spell or spell haltingly, and have difficulty concentrating. The application of the sorogan method can provide an alternative to improve students' reading skills.